Designing a pilot model for fully digitalised internal examinations in urban secondary schools: a sustainable transition framework - Chi, Wen Jye (Frontiers in Education, 2026)
Many schools are using digital tools more frequently in day-to-day lessons, yet important national exams continue to be conducted on paper. This creates a practical tension: Students become familiar with digital work in class but are still required to perform in a paper-based setting during high-stakes assessments. This article introduces a small-scale change management initiative for schools that wish to explore a more sustainable way of integrating digital assessments. The focus is on urban secondary schools with students aged approximately 15 to 17 years. In developing the framework, Kotter’s 8-Step Model is used to organise the school-level process, while the Technology Acceptance Model (TAM) helps explain how teachers, students, and other staff members might respond to the transition. The model could later be examined in other urban settings to assess how far its ideas can be applied. The proposed pilot encourages schools to digitalise internal assessments, classroom tasks, and learning materials while maintaining readiness for paper-based national examinations through the use of occasional hybrid practices. To understand the effects of the pilot, the evaluation will draw on indicators such as student achievement, digital skill growth, levels of engagement, and environmental impact. These indicators can be supported by existing datasets, including national device-ownership figures and OECD reports. Overall, the framework aims to prepare schools gradually for future online and distance learning while maintaining stability in current examination performance.